Non-Malleable Code in the Split-State Model - Divesh Aggarwal; Marshall Ball; Maciej Obremski (Entropy, 2022)
Non-malleable codes are a natural relaxation of error correction and error detection codes applicable in scenarios where error-correction or error-detection is impossible. Over the last decade, non-malleable codes have been studied for a wide variety of tampering families. Among the most well studied of these is the split-state family of tampering channels, where the codeword is split into two or more parts and each part is tampered with independently. We survey various constructions and applications of non-malleable codes in the split-state model.